Therapeutic Potency of Mono- and Diprenylated Acetophenones: A Case Study of In-Vivo Antimalarial Evaluation - Yahya, Muhammad H.; Babalola, Sodeeq A.; Idris, Abdullahi Y.; Hamza, Asmau N.; Igie, Nosakhare; Odeyemi, Isaiah; Musa, Aliyu M.; Olorukooba, Amina B. (Pharmaceutical Fronts, 2023)
Malaria remains a febrile infection of public health concern in many countries especially tropical countries in Africa and certain countries in Southern and North America such as Brazil, Costa Rica, Mexico, Dominican Republic, Colombia, and Ecuador. Hence this has made research into this area paramount. Acetophenones are active fragments in many compounds with promising antimalarial activity, such as chalcones. The aim of the present study was to investigate antimalarial activity of 3,5-diprenyl acetophenone (I) and 5-diprenyl acetophenone (II) in in vivo. In this study, compounds I and II were synthesized using an aromatic substitution reaction. The in-vivo antimalarial potential of compounds I and II was analyzed in Plasmodium berghei-infected mice. Our data showed that compound I (25, 50, and 100 mg/kg) had promising antimalarial activity, with parasitemia inhibited rate being 68.03, 65.16, and 69.75%, respectively. Compound II dose-dependently inhibited parasitemia levels, it demonstrated an infinitesimally higher activity (72.12%) when compared with compound I (69.75%) at 100 mg/kg dose. The two compounds passed the rule of three, Lipinski's rule of five, predicted plausible pharmacokinetic profile (ADME), and apparent safety profile, and demonstrated drug-like fragments. The study provided guidance in exploring novel antimalarial compounds based on the scaffolds of prenylated acetophenones.
Keywords: malaria; prenylated acetophenone; 3,5-diprenyl acetophenone; 5-diprenyl acetophenone; fragment-based drug design